Non-invasive bladder cancer - Burger, Maximilian; Schwaibold, Hartwig; Goebell, Peter; Grimm, Marc-Oliver (Onkologe, 2018)
Background. Non-muscle-invasive bladder cancer is a common cancer entity demanding complex diagnostics and treatment. Aim. This review presents the current state of the art of the diagnostics and treatment with an emphasis on risk-adapted patient management. Material and methods. This review is based on a literature search in PubMed for sources on the etiology, diagnostics, treatment and risk-adapted patient management of non-muscle-invasive bladder cancer. Results. Non-muscle-invasive bladder cancer mainly becomes clinically apparent with painless macrohematuria. Only cystoscopy can lead to a sufficiently sound diagnosis, whereas no urinary markers providing reliable accuracy exist. Treatment usually starts with transurethral resection of the bladder tumor providing histopathological verification of the diagnosis and a basis for further treatment: in some cases it is the only treatment necessary. Histopathology guides further decision-making and provides a clear risk stratification by using some simple clinical and cystoscopical parameters. In low-risk cases transurethral resection with a single adjuvant instillation therapy early after surgery suffices, in intermediate-risk cases further outpatient instillations with a chemotherapeutic agent or bacillus Calmette-Gu,rin (BCG) follow and in high-risk cases resection is followed by repeat resection and BCG; however, cystectomy also has to be considered. In all cases a structured follow-up is mandatory. Conclusion. Despite high recurrence rates and in high-risk cases also substantial progression rates of non-muscle-invasive bladder cancer, a relatively good prognosis concerning recurrence and an advantageous prognosis concerning cancer-specific survival can be achieved using all currently available possibilities.
EVALuna2:35907